Streamlined break scheduling for major track repairs - Vyacheslav G. Fedulin; Mikhail I. Mehedov; Vladimir A. Antonets; Vladimir A. Ustinov (Вестник Научно-исследовательского института железнодорожного транспорта, 2024)
Introduction. Overhaul of railway track and routine maintenance of infrastructure requires interruptions in train traffic. This has a major impact on transport and at the same time is an integral part of it. Allocation of interruptions in traffic is based on the prioritisation of clearance for trains, which often complicates repairs of a given scope. The article considers ways to streamline break scheduling for railway repairs on heavy-traffic routes.Materials and Methods. The research is based on the known theories of operational management of transportation, applied technologies of infrastructure repair, statistics of clearance for trains, repair scopes and variable train schedules. The paper uses methods for calculating the capacity of space intervals under repair, and theoretical justification of analytical formulas for calculating clearance for trains.Results. The paper highlights calendar periods and redefines traffic capacity indicators and their calculation methods for determining the annual average daily throughput capacity. The article plots possible track overhaul schedules with different durations and different interruption patterns (breaks). The work shows the dependencies of the total duration of breaks and total clearance for trains during a calendar year under different repair patterns for selecting a variant under given conditions.Discussion and conclusion. These dependencies help streamline the repair programmes considering repair volumes and clearance for trains at the scheduling stage. Automation of the process optimises labour costs for scheduling repairs.